An updated investigation on the antenatal development of the thyroid gland in white New Zealand rabbit with morphometric analysis - Moselhy, Attia A.A.; Nosseur, Hamed M.; El-Sayed, Sahar M.; Konsowa, Mervat M.H. (Journal of Advanced Veterinary Research, 2024)
The prenatal development of the thyroid gland was studied on 30 rabbit embryos and fetuses of both sexes. Their ages ranged between 9th days old till the day of birth. The thyroid anlage appeared as an endodermal thickening in the floor of the primitive pharynx at 9th days of gestation. At 11th days old embryos, the thyroid bud was connected to the pharyngeal endoderm by the thyroglossal duct which began to disintegrate at 12th days of gestation. The bilobation of primitive thyroid gland was exhibited with the beginning of isthmus organization at 16th days of gestation. The first evidence of follicular organization appeared at 20th days of gestation with many small follicles disseminated within the gland. The first morphological sign of functional differentiation of the thyroid gland appeared at 22nd days of gestation as PAS positive thick rim of pre colloid material in apical parts of the follicular cells in some follicles. Very few parafollicular cells began to scatter among follicular cells at 22nd days old fetuses. The definitive thyroid follicles storing vacuolated typical colloid organized at 28th days of gestation and stained somewhat strongly with Eosin and PAS.